The Effect of Shopee E-Commerce on the Consumptive Behavior of Students of the Department of Social Science Education, Faculty of Teacher Training and Education, Mulawarman University - Musdalipa, Musdalipa; Ellyawati, Noor; Sutrisno, Sutrisno (Faculty of Teacher Training and Education, Mulawarman University, 2023)
The emergence of E-commerce Shopee can cause changes in student consumption behavior. The massive promos offered by E-commerce Shopee will encourage students to shop and tend to behave consumptively. The purpose of this research is to determine the effect of Shopee E-commerce on student consumptive behavior. This type of research uses quantitative research methods with a population of 258 students majoring in social science education, Faculty of Teacher Training and Education, Mulawarman University, and a sample size of 72 students where the sample is obtained by using the Slovin formula. The data collection technique was carried out by distributing questionnaires to respondents. This study uses classical assumption test data analysis techniques in the form of normality tests, heteroscedasticity tests, simple linear regression tests and coefficient of determination tests, and uses the t test to test hypotheses. The results showed that Shopee E-commerce had a significant effect on the consumptive behavior of students majoring in social science education, Faculty of Teacher Training and Education, Mulawarman University. This can be seen from the results of the t test, where t_hitung is greater than t_table (2.072> 1.994), with a significant level smaller than 0.05 (0.042 <0.05). Based on statistical data testing through the analysis of the coefficient of determination, it can be seen that the coefficient of determination (R^2) is 0.058 or 5.8%, which means that variable X (Shopee E-commerce) affects variable Y (consumptive behavior) 5.8%. Another 94.2% is influenced by other variables not explained in this study. Based on the research results it can be concluded: E-commerce Shopee affects the consumptive behavior of students of the Social Science Education Department, Faculty of Teacher Training and Education, Mulawarman University.